Studi Kelayakan Kesiapan Bumdes Ngingas Makmur Abadi, Waru-Sidoarjo Sebagai Cluster Teaching Industry Dalam Mendukung Konsep Merdeka Belajar Kampus Merdeka (MBKM) - Handiwibowo, Gogor Arif; Suef, Mokhamad (Universitas katolik Musi Charitas, 2021)
The Merdeka Belajar Kampus Merdeka (MBKM) concept has been rolled out by the Minister of Education and Culture of the Republic of Indonesia in 2020. This program adopts a structured and programmed independent learning pattern outside the classroom. In science and technology-based higher education institutions, the MBKM concept is in line with the teaching industry concept where in this concept the learning process is carried out by utilizing the activities of a particular industry as a learning base. In this paper, a feasibility study of BUMDes Ngingas Makmur Abadi will be discussed to become a teaching industry from the Institut Teknologi Sepuluh Nopember (ITS) – Surabaya to support the concept of Merdeka Belajar Kampus Merdeka (MBKM). Through qualitative analysis of interview data with the director of BUMDes Ngingas Makmur Abadi and through a survey of business activities, it was stated that BUMDes Ngingas Makmur Abadi deserves to be one of the cluster teaching industries of the Institut Teknologi Sepuluh Nopember (ITS) – Surabaya with a manufacturing sector. Through this teaching industry, each party (BUMDes Ngingas Makmur Abadi and ITS) will get benefits that can be used to improve their respective competencies.